Pengaruh Manajemen Risiko terhadap Kinerja Operasional Pelabuhan Rakyat Paotere Makassar - Dianita Veronika Lantang; Fahirah Salahuddin; St. Zaenab Achmar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of risk management on operational performance at the Paotere People's Port, Makassar. The research approach used is quantitative with an explanatory method to explain the causal relationship between variables. Data were collected through questionnaires distributed to 45 operational employees selected using a saturated sampling technique. The research instrument was tested for validity and reliability using SPSS 23, and all statement items were declared feasible. Data analysis was conducted through simple linear regression to test the influence of risk management variables on operational performance. The results showed that risk management has a positive and significant effect on operational performance. This finding indicates that improving the quality of risk management can encourage the effectiveness and efficiency of port operational activities. This study emphasizes the importance of implementing systematic risk management to support the stability and performance of people's port services.